2017
DOI: 10.1111/jai.13587
|View full text |Cite
|
Sign up to set email alerts
|

Age determination and growth estimates of the white-spotted conger eel, Conger myriaster (Brevoort, 1856) in marine waters of South Korea

Abstract: Summary The age and growth of conger eel, Conger myriaster, were investigated by measuring transversely sectioned sagittal otoliths samples from 635 individuals. Sample ages ranged from 1 to 13 years in the female data. Parameters of the von Bertalanffy growth function were estimated using nonlinear regression from back‐calculation, mean length of samples at age relationships, and otolith weight‐at‐age relationships. Best‐fitting value of the three methods was the otolith weight‐at‐age relationship (r2 = .87).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Our study suggested that the fitted growth models using model-based age and counted age were not significantly different, implying that otolith annuli analyses may not be necessary to growth analyses, instead, otolith and fish morphometrics can be used. Besides, the L ∞ and K estimated in the present study are similar to those reported in the Southern water of Korea [ 14 , 35 ], supporting the usability of this approach.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study suggested that the fitted growth models using model-based age and counted age were not significantly different, implying that otolith annuli analyses may not be necessary to growth analyses, instead, otolith and fish morphometrics can be used. Besides, the L ∞ and K estimated in the present study are similar to those reported in the Southern water of Korea [ 14 , 35 ], supporting the usability of this approach.…”
Section: Discussionsupporting
confidence: 89%
“…Studies suggested that the morphometrics of otoliths may provide critical information for aging when annuli is less useful. Radtke (1985) explored the utility of otolith weight to estimate ages of fish [ 12 ], and otolith morphometrics have been successful applied to determine age of eels [ 13 14 ]. In addition, age and total length (TL) are usually correlated, so somatic morphometrics could also be used for age determination [ 15 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The monthly variation in relative abundance and distribution of whitespotted conger based on the conclusion of modeling indicated a feeding, wintering, and spawning migration for individuals of different sizes in the survey areas (Mu et al, ; Tokimura, ), which was consistent with the similar study of Katayama, Ishida, Shimizu, and Yamanobe (). The likely movement pattern of whitespotted conger could be inferred from the predicted maps based on the previous studies (Bae et al, ; Zhu, Zhang, & Cheng, ). The large and relatively smaller individuals of this conger species were found to migrate to the offshore area and began their southward spawning migration and wintering migration in late autumn in the Yellow Sea, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…However, Food and Agriculture Organization of the United Nations (FAO) fact sheet ignored the distribution along coastal China for this conger species, and the population trend and distribution of whitespotted conger in China has not been studied (Guillotreau, Bundy, & Perry, ). A further understanding of the population status and distribution of conger is largely needed for the sustainable exploitation of viable populations (Bae et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation